Hadith Genre, Qasasul-AnbiyÄÊ¾, and IsrÄÊ¾Ä«liyyÄt:: A Genre-Critical Reading of Roberto Tottoli - Diah Yuliarizki; Zalfa Qothrun Nada (El Nubuwwah Jurnal Studi Hadis, 2026)
Contemporary Hadith studies have increasingly been framed within a rigid dichotomy between the normative approach, which regards Hadith as an authoritative religious source, and revisionist historiographical approaches that primarily question its historical authenticity. This polarization has left unresolved scholarly debates concerning the fluid boundaries between Prophetic Hadith, Qiá¹£aá¹£ al-AnbiyÄÊ¾, and IsrÄÊ¾Ä«liyyÄt in the formative period of Islamic literature. This study aims to reconstruct the implications of Roberto Tottoli's theory of genre fluidity for redefining Hadith as a literary category while examining its interaction with IsrÄÊ¾Ä«liyyÄt narratives in early Islamic literary traditions. Employing a qualitative library-based approach, this research adopts a figure-study method by critically examining Tottoli's principal works through genre criticism and placing them in dialogue with the epistemological perspectives of classical Hadith scholars, particularly Ibn al-á¹¢alÄá¸¥, Ibn Taymiyyah, and Ibn KathÄ«r. The findings demonstrate that during the pre-tadwÄ«n period, the boundaries between Hadith, historical narratives, Qiá¹£aá¹£ al-AnbiyÄÊ¾, and IsrÄÊ¾Ä«liyyÄt remained fluid and mutually interconnected. In contrast, the post-tadwÄ«n period witnessed the gradual establishment of disciplinary boundaries through the epistemology of isnÄd and textual verification, distinguishing canonical Prophetic traditions from broader narrative traditions. This study proposes a dialogical synthesis in which Hadith is understood simultaneously as a literary genre that evolved historically and as a normative source whose authority was secured through the epistemological framework of classical Hadith scholarship, thereby contributing a more balanced perspective to contemporary Hadith Studies.